Discussions on Education in Serbia During the COVID-19 Lockdown: A Twitter-Based Analysis - Jovanović , Olja; Gagić, Dragana; Radaković, Tatjana; Barišić, Milica; Vuliš Šimšić, Ivana (Psihološka istraživanja, 2025)
The COVID-19 pandemic led to unprecedented changes across various aspects of life worldwide, including a significant impact on the education systems. This study aimed to explore the public perception of education during the initial five weeks of emergency remote education (ERE) implementation in Serbia in response to the COVID-19 outbreak. Using the Cultural-Historical Activity Theory (CHAT) as a framework, we collected and analyzed posts on the social media platform Twitter. The tweets on the topic of education were retrieved using MAXQDA software starting from March 17, 2020 and over the next 5 weeks, resulting in a final dataset of 1,777 tweets. The results of the research show a decreasing trend in the frequency of posts related to education, starting from 1,402 in the first week to 92 tweets in the fifth week. The emotional tone of the tweets was predominantly negative in the first five weeks of the pandemic, with the percentage of tweets with a negative connotation tending to increase. The analysis of the content of the tweets highlights key themes and reveals contradictions between ERE and conventional schooling. The Twitter community praised the use of new tools and teachers’ efforts, but criticized adhering to the rules of the conventional schooling as well as the learning content as being overly demanding and irrelevant. The study results suggest that ERE during the lockdown increased the visibility of teaching, offering potential for educational democratization, while the invisibility of learning created risks to educational equity by obscuring the struggles of learners.